2018
DOI: 10.1371/journal.pone.0207822
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre study investigating parameters which influence direct bacterial identification from urine

Abstract: Rapid diagnosis is one of the best ways to improve patient management and prognosis as well as to combat the development of bacterial resistance. The aim of this study was to study parameters that impact the achievement of reliable identification using a combination of flow cytometry and matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-ToF-MS).The study was carried out in nine hospitals in Spain and included 1,050 urine samples with bacterial counts of 5x106 bacteria/ml. MALD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…While Zboromyrska et al used 10 mL of urine with bacterial counts of ≥5,000 bacteria/μL for MALDI-TOF MS direct identification and obtained high scores (Zboromyrska et al, 2016). Moreover, these parameters were confirmed by a multicentre study that followed soon after (Zboromyrska et al, 2018).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…While Zboromyrska et al used 10 mL of urine with bacterial counts of ≥5,000 bacteria/μL for MALDI-TOF MS direct identification and obtained high scores (Zboromyrska et al, 2016). Moreover, these parameters were confirmed by a multicentre study that followed soon after (Zboromyrska et al, 2018).…”
Section: Discussionmentioning
confidence: 60%
“…For this study, 1,638 urine samples submitted to our clinical microbiology laboratory with sufficient volumes were screened for bacteria through a UF-1000i cytometer. Based on a previously established bacterial counts cut-off value of ≥5,000 bacteria/μL (Zboromyrska et al, 2016, 2018), 307 (18.74%) out of 1,638 samples were positive and used for further direct identification. Among these positive samples, 265 had a significant growth of a single microorganism by urine culture, 16 had a significant growth of two microorganisms, 22 were contaminated, and 4 were negative (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before extraction with formic acid and acetonitrile, both are subjected to low-speed centrifugation to eliminate human cells [ 10 , 17 , 36 ]. For the processing of urine samples specifically, an initial flow cytometric scan is recommended to eliminate negative urine and limit direct processing to urine with counts greater than 10 5 colony forming units per millilitre (CFU/mL) [ 17 , 24 , 37 ]. Recently, various research groups have proposed different extraction methods based on differential centrifugations [ 37 , 38 ], ultrafiltration [ 39 ], or a simple pre-treatment of samples with sodium-dodecyl-sulfate (SDS) [ 40 , 41 ].…”
Section: Direct Microbial Identification From Human Samplesmentioning
confidence: 99%
“…For the processing of urine samples specifically, an initial flow cytometric scan is recommended to eliminate negative urine and limit direct processing to urine with counts greater than 10 5 colony forming units per millilitre (CFU/mL) [ 17 , 24 , 37 ]. Recently, various research groups have proposed different extraction methods based on differential centrifugations [ 37 , 38 ], ultrafiltration [ 39 ], or a simple pre-treatment of samples with sodium-dodecyl-sulfate (SDS) [ 40 , 41 ]. A recent study conducted by Veron and colleagues [ 42 ] compared centrifugation (68.4% of correct MALDI identification), urine filtration (78.9%) and 5 h bacterial cultivation on solid culture media (84.2%), which demonstrated that a short culture step is the most straightforward and efficient sample preparation method for fast and reliable identification of uropathogens.…”
Section: Direct Microbial Identification From Human Samplesmentioning
confidence: 99%